2018
DOI: 10.3389/fimmu.2018.00797
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprogressive Disease in Anorectal Melanoma Treated by PD-1 Inhibitors

Abstract: The 5-year survival rate of primary anorectal malignant melanoma is less than 20%. Optimal treatment of this condition remains controversial regarding locally disease, and whether any preferential survival benefit arises from either abdominoperineal resection or wide local excision remains unknown. The majority of patients progress to metastatic disease, and for decades, the use of chemotherapies, such as platines or dacarbazine, has been advocated to improve overall survival. The therapeutic use of new checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…[27]. Later, an anorectal melanoma patient with hyperprogressive disease under anti-PD-1 therapy was reported [26]. In this second case, however, no information was provided on MDM2/4 or EGFR amplification.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[27]. Later, an anorectal melanoma patient with hyperprogressive disease under anti-PD-1 therapy was reported [26]. In this second case, however, no information was provided on MDM2/4 or EGFR amplification.…”
Section: Introductionmentioning
confidence: 93%
“…Not all of these criteria were always met, such as when authors dealt with the term "hyperprogression". In some case series, staging intervals of three months and more were also included and progression speed was not always calculable [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…83 This situation has also been noted anecdotally in melanoma. 84 While the mechanism of this hyperprogressive response to presumed anticancer agents remains unclear, the proposed model suggests a number of testable hypotheses that are concordant with an initial suggestion that activation of the microenvironmental tumor associated macrophages contribute to this perverse outcome. 85 This would represent yet another mechanism for escape from treatments.…”
Section: Avoidance Of the Micrometastasesmentioning
confidence: 76%
“…In some case reports, patients rapidly declined and died without any subsequent therapy . A case report detailing post‐pembrolizumab hyperprogression in an anorectal melanoma patient reported that the patient received one cycle of dacarbazine without clinical improvement . In fact, most of the studies thus far recommend avoiding future immunotherapy use altogether in this subgroup given the risks of hyperprogression.…”
Section: Discussionmentioning
confidence: 99%